MathAIde in the Classroom: A Qualitative Analysis of Teachers' Perspectives of Intelligent Tutoring Systems Unplugged - Rodrigues, Luiz; Guerino, Guilherme; Veloso, Thomaz E. V. da; Bianchini, Luana P.; Xavier, Mariana X. M. S.; Vieira, Thales; Marinho, Marcelo; Macario, Valmir; Dermeval, Diego; Bittencourt, Ig Ibert; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na Educação, 2024)
Intelligent Tutoring Systems (ITS) have shown significant promise in enhancing math education by providing personalized and adaptive learning experiences. However, their adoption in resource-constrained environments is limited by the need for dedicated computing devices for each student. To address this issue, the concept of ITS unplugged has emerged, which helps deliver ITS benefits in resource-constrained settings, for instance, without the necessity for individual computers. However, past research has not investigated how ITS unplugged contributes to mathematics education when deployed in real classrooms. This paper presents a qualitative evaluation of MathAIde, an ITS unplugged designed to support numeracy education, where three teachers used MathAIde in 12 lessons, involving 49 students, and their experiences were captured through semi-structured interviews. Thematic analysis revealed that MathAIde facilitated lesson planning and execution, provided valuable feedback and learning analytics, but faced challenges such as technical issues and the need for more adaptive content. This study contributes empirical evidence on the impact of ITS unplugged in real classrooms, offering insights for future development and adoption of such technologies to promote equitable access to ITS benefits in education.